The king's deception : a novel - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2013)
When escalating political tensions between the United States and England put his son, Gary, in the hands of a man with a shadowy and intensely personal agenda, Cotton Malone finds himself confronting a baffling historical mystery that questions the legitimacy of Elizabeth I.